Distribution of Cadmium in Seawater, Sediment and Soft Tissue of Bivalve in Van Don Coastal in Quang Ninh, Vietnam - Thien, Luu Ngoc; Thanh, Nguyen Cong (Asian Journal of Chemistry, 2018)
Level of cadmium were determined in coastal water, sediments and soft tissues molluscs hakf-crenate ark (Anadara subcrenata), noble scallop (Mimachlamys nobilis) and undulating venus (Paphia undulata), from two stations in bivalves harvesting areas in Van Don, Quang Ninh province. In this study, cadmium concentration in seawater ranged between 0.22 to 1μg.L-1 while that concentration in sediment were from 0.59 to 1.55 mg kg-1. Accumulate cadmium in hakf-crenate ark (Anadara subcrenata), noble scallop (Mimachlamys nobilis) and undulating venus (Paphia undulata) were from 0.81 to 1.48 mg kg-1; from 0.35 to 2.23 mg kg-1; from 0.25 to 0.81 mg kg-1, respectively. The result also show that the cadmium in seawater in rain season were higher dry season while reversibility trend in sediment. The cadmium fraction in sediment in this area were contributed according to follow: residual component (F5) > Mn, Fe oxyhydroxide (F3) > organic matter-bound (F4) > acid soluble (F2) > ion-changeable (F1). Cadmium levels in tissue were in the order of stomach > mantle > gill > foot. Beside, cadmium component in adductor muscle of noble scallop were least. The results of study could serve as a baseline for future assessments of anthropogenic effect in this coastal and food safety problems.